Cerebral palsy: Oral manifestations and dental management - Karaseridis Konstantinos; Dermata Anastasia (Balkan Stomatological Society, 2023)
Cerebral palsy is a set of non-progressive neuromuscular disorders caused by defects in the developing fetal brain. Its prevalence is about 2:1000. Although CP does not directly result in any particular oral abnormalities, some conditions are more prevalent or severe in CP patients than in the general population. The purpose of a paediatric dentist is to promote overall oral health wellness and to motivate parents and other primary caregivers to practice good oral hygiene at home. The aim of this article is to provide a general overview of dental health issues that affect people with CP and to analyze key preventative and practical management techniques for this common comorbidity.